2020
DOI: 10.1007/s10071-020-01432-w
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric spatial behaviour in rats reveals the anisotropic organisation of navigation

Abstract: We investigated how access to the vertical dimension influences the natural exploratory and foraging behaviour of rats. Using high-accuracy three-dimensional tracking of position in two- and three-dimensional environments, we sought to determine (i) how rats navigated through the environments with respect to gravity, (ii) where rats chose to form their home bases in volumetric space, and (iii) how they navigated to and from these home bases. To evaluate how horizontal biases may affect these behaviours, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 135 publications
(226 reference statements)
4
8
0
Order By: Relevance
“…Given previous findings that place cells express spatially localized firing fields in volumetric space 7 and that rats can navigate accurately in the lattice maze 17 , 18 , our results suggest that place cells and spatial mapping can perhaps function even when grid cell firing fields are irregularly distributed 18 . It may be that place cells do not require grid cell inputs for positioning when visual cues are available 28 , although future studies that simultaneously record place and grid cells in three dimensions, in the presence and absence of visual cues, are needed to fully explore this relationship.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Given previous findings that place cells express spatially localized firing fields in volumetric space 7 and that rats can navigate accurately in the lattice maze 17 , 18 , our results suggest that place cells and spatial mapping can perhaps function even when grid cell firing fields are irregularly distributed 18 . It may be that place cells do not require grid cell inputs for positioning when visual cues are available 28 , although future studies that simultaneously record place and grid cells in three dimensions, in the presence and absence of visual cues, are needed to fully explore this relationship.…”
Section: Discussionsupporting
confidence: 71%
“…We considered a ‘crossing’ to have occurred when the head of the rat moved from one unit to another. A detailed analysis of the behavioral data can be found elsewhere 17 and so only brief results related to grid cell activity are reported in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, our converging results from the structure mapping task as well as from the M-TSP task provide new behavioural evidence for a horizontal bias in volumetric spatial cognition and behaviour. This is in line with the literature from animal research (Grieves et al, 2021;Jedidi-Ayoub et al, 2021;Jovalekic et al, 2011). We have also…”
Section: Synthesissupporting
confidence: 93%
“…An alternative explanation is that there is a difficulty associated with externalising representations of 3D space on a 2D space medium. Overall this results supports the theory of anisotropy of organisation of cognitive maps (Brandt et al, 2015;Jedidi-Ayoub et al, 2021) and the theory of horizontal bias (Jovalekic et al, 2011).…”
Section: Mental Representations Of Volumetric Spacesupporting
confidence: 86%
“…Rodents set their home-base near a salient landmark [ 19 ], which in an empty arena (open-field) is usually in one of the corners, perhaps due to the sense of safety [ 20 , 21 ]. In more complex environments, it was found that rats tend to set their home-base at a vantage point [ 22 ]. The majority of studies on spatial behavior in rodents was performed in two-dimensional laboratory environments.…”
Section: Introductionmentioning
confidence: 99%